Mathematical Analysis of Electric Power Replacement Schemes of Weaving Machines - Khafizov, Islom; Gafforov, Komil; Yormamatov, Bahodir (European Journal of Life Safety and Stability (2660-9630), 2021)
At present, a lot of attention is paid to the processing of raw cotton and its delivery to consumers in the form of fabrics or ready-made clothes. Over the years, a series of modern and improved workbenches have been developed. This article aims to increase the energy efficiency of the Optimax-i-4-R loom by mathematically analyzing the replacement shops of asynchronous machines used in looms.